Perception of Consequences of Suicide Among Educated Adults in Ondo Metropolis, Nigeria - Soetan, Margaret Kehinde (Teaching, Learning, and Development, 2026)
This study investigated perception of consequences of suicide among educated adults. Descriptive survey research design was adopted in the study. The population comprised all educated adults in Ondo metropolis. Random sampling technique was used to select two hundred (200) educated adults as sample for the study. Structured questionnaire titled “Questionnaire on Suicide” (QS) was used as instrument to collect data for the study. Reliability of the instrument was ascertained using Cronbach’s Alpha statistics which yielded a coefficient of 0.91. Data collected was analysed using mean, ranking, t-test and Analysis of Variance. The results showed consequences of suicide as emotional suffering of the families, wastage of resources in terms of medical care, lost productivity and emotional suffering of the communities in descending order. It was also found that gender has a significant influence on perception of consequences of suicide while marital status and religion do not. It was therefore recommended that family should be closely knit and consider mental health of members very paramount. Families should monitor members with mental illness for social and psychological support. All avenues should be used to sensitize communities to prevent suicide. Mostly affected sex should be identified for intensive prevention move. All religions should work collaboratively for the prevention of suicide.